(Un)Intentional Community: Power and Expert Knowledge in a Sustainable Lifestyle Community*. Issue 4 (17th June 2016) - Sullivan, Esther
Abstract : This ethnography of a cohousing organization examines power and expert knowledge in a sustainable intentional community. Intentional communities are forming at a growing rate both internationally and in the United States. Cohousing communities are part of this growing trend of alternative communities that utilize participatory democracy as both their central decision‐making process and a core component of their alternative identity. This article analyzes the tensions that evolve as cohousers build a communal housing development in one of the fastest‐growing cities in the United States. I identify mechanisms through which the constraints of operating in the highly professionalized field of housing development transform participatory decision making. When group members try to minimize loss of time and capital while competing with experienced for‐profit developers, they establish leaders and cede power to those with greater technical expertise. Yet, they continue to model their commitment to consensus decision making despite emerging hierarchies among members. I describe how the use of expert knowledge restructures the conditions governing group interaction and explore what the group's oligarchic organizational practices mean for the study of contemporary collective community organizing.